2018
DOI: 10.3389/fpls.2018.00535
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Yield and Nutritional Quality of Forage Crops

Abstract: Despite being some of the most important crops globally, there has been limited research on forages when compared with cereals, fruits, and vegetables. This review summarizes the literature highlighting the significance of forage crops, the current improvements and some of future directions for improving yield and nutritional quality. We make the point that the knowledge obtained from model plant and grain crops can be applied to forage crops. The timely development of genomics and bioinformatics together with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
120
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 211 publications
0
120
0
2
Order By: Relevance
“…Forage biomass yield is one of the major targets in forage crop improvement, where fast-growing and high LSR types are preferred [34]. The current study revealed that TFW and TDW were higher in the wet season than in the dry season, indicating that moisture availability was a determinant factor for growth and development of Napier grass.…”
Section: Forage Yield Of Napier Grass Genotypesmentioning
confidence: 52%
“…Forage biomass yield is one of the major targets in forage crop improvement, where fast-growing and high LSR types are preferred [34]. The current study revealed that TFW and TDW were higher in the wet season than in the dry season, indicating that moisture availability was a determinant factor for growth and development of Napier grass.…”
Section: Forage Yield Of Napier Grass Genotypesmentioning
confidence: 52%
“…Fluctuations in seed development and subsequent yield in Siberian wildrye, as in many other grass species, may be influenced by growing conditions, physiological processes underlying assimilates production and partitioning and molecular genetic factors [6,7]. Consequently, forage breeders have mainly focused on increasing biomass yield and enhancing forage quality [8]. Despite this, seed yield remains a decisive factor for a cultivar success in this species and understanding traits determining seed yield potential is imperative [2].…”
Section: Introductionmentioning
confidence: 99%
“…and herbaceous legumes (e.g., Lotus spp., Medicago spp., and Trifolium spp.) [9]. This review will be focused on the use of these type of pastures.…”
Section: Introductionmentioning
confidence: 99%